Persistent Primitive Trigeminal Artery: An Unusual Cause of Vascular Tinnitus. (29th December 2013) - Panda, Ananya; Arora, Arundeep; Jana, Manisha
Abstract : Pulsatile tinnitus is generally of vascular origin and can be due to arterial, venous, or systemic causes. While certain congenital anatomical variants and arterial vascular loops have been commonly found in symptomatic patients undergoing imaging, persistent primitive trigeminal artery in association with isolated tinnitus is unusual. Thus we report a patient with unilateral isolated pulsatile tinnitus who was evaluated with magnetic resonance angiography and was found to have a persistent primitive trigeminal artery. We also briefly discuss vascular tinnitus as well as the embryology, imaging, and classification of persistent primitive trigeminal artery with the clinical implications.